Digital Control of Bonding Force for Gold Wire Bonding Machine - Xiaochu Wang; Zhongjun Zhu; Jian Gao; Xin Chen; Yonggang Wu (Institute of Advanced Engineering and Science, 2013)
In order to digitally control the bonding force of a wire bonder precisely, this paper uses a DC solenoid as a force source, and by controlling the solenoid’s current, which causes the electromagnetic force, we can control the bonding force that capillary applies. The bonding force control system in this paper is composed of PC (Personal Computer) and hypogyny MCU (Micro Controller Unit), which communicate using a RS485 interface. The digital value of a given bonding force is given by the PC to the MCU. By comparing the sampling current of the solenoid, and through PID regulation, D/A converter of the digital potentiometer and the solenoid driver circuit, the half-closed loop control system of bonding force is accomplished. Tuning of the PID parameters is accomplished with fuzzy adaptive control theory and simulated by Matlab simulink. The control system is tested by comparing the desired bonding force and the force actually applied and examming the relationship between bonding quality and bonding force. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2306